[tex]1)\\\\y=-x^2-2x+3 \\\\postac \ iloczynowa:\\\\y=a(x-x_{1})(x-x_{2}) \\\\a=-1,\ \ b=-2,\ \ c=3\\\\\Delta =b^2-4ac=(-2)^2-4*(-1)*3=4+12=16\\\\\sqrt{16}=4\\\\x_{1}=\frac{-b-\sqrt{\Delta }}{2a}=\frac{2-4}{2*(-1)}=\frac{-2}{-2}=1[/tex]
[tex]x_{2}=\frac{-b+\sqrt{\Delta }}{2a}=\frac{2+4}{2*(-1)}=\frac{6}{-2}=-3\\\\y=-(x-1)(x+3)[/tex]
[tex]2)\\\\y=-x^2+x+6 \\\\a=-1,\ \ b=1,\ \ c=6\\\\\Delta =b^2-4ac=(-1)^2-4*(-1)*6=1+24=25\\\\\sqrt{25}=5\\\\x_{1}=\frac{-b-\sqrt{\Delta }}{2a}=\frac{1-5}{2*(-1)}=\frac{-4}{-2}=2[/tex]
[tex]x_{2}=\frac{-b+\sqrt{\Delta }}{2a}=\frac{1+5}{2*(-1)}=\frac{6}{-2}=-3\\\\y=-(x-2)(x+3)[/tex]